2020
DOI: 10.26656/fr.2017.4(4).029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus plantarum and Leuconostoc mesenteroides starter cultures in lower salt concentration fermentation on the sauerkraut quality

Abstract: This research was aimed to study the effect of Lactobacillus plantarum and Leuconostoc mesenteroides starter cultures application in lower salt concentration fermentation on sauerkraut quality. Fresh cut cabbage was fermented with different starter cultures (L. plantarum, L. mesenteroides or the combination) at different lower salt concentration (0.5% or 1%) at 28oC for 5 days. The obtained sauerkrauts were subjected to evaluation of the quality i.e. total lactic acid bacteria, pH, total acidity, total phenoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
(34 reference statements)
3
3
0
1
Order By: Relevance
“…Regarding DPPH assay, the highest value was found after 24-h fermentation (4.57 ± 0.25 mg TE/g sample). After it reached its peak at 24-h fermentation, it gradually decreased after 72-h fermentation, and the DPPH radical scavenging ability returned to its initial value after 168 h. This result is in agreement with earlier reports [34,41,42]. In the ABTS assay, the maximum value was found after 24-h and 72-h fermentation (4.91 ± 0.08 and 4.91 ± 0.40 mg TE/g sample), respectively, while the minimum value was seen after 168-h fermentation (3.59 ± 0.08 mg TE/g sample).…”
Section: Antioxidant Activitiessupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding DPPH assay, the highest value was found after 24-h fermentation (4.57 ± 0.25 mg TE/g sample). After it reached its peak at 24-h fermentation, it gradually decreased after 72-h fermentation, and the DPPH radical scavenging ability returned to its initial value after 168 h. This result is in agreement with earlier reports [34,41,42]. In the ABTS assay, the maximum value was found after 24-h and 72-h fermentation (4.91 ± 0.08 and 4.91 ± 0.40 mg TE/g sample), respectively, while the minimum value was seen after 168-h fermentation (3.59 ± 0.08 mg TE/g sample).…”
Section: Antioxidant Activitiessupporting
confidence: 93%
“…The gradual rise of phenolic content from the starting phase of the fermentation to 168-h fermentation may be due to the increase in bioactive compounds, such as phenolic acids, through LABmediated fermentation [32,33]. The increase in phenolic contents was further explained by Zubaidah et al [34], in which, during fermentation, complex bonds between phenolic and other compounds were broken by enzymes, such as invertase, cellulase, and amylase, leading to the increase in total phenolic content. In this study, a slight decrease in phenolic content at 120-h fermentation may be related to the fact that the phenolics of coffee pulp extract might bind with sugar , leading to reduced solubility of phenolic compounds, or it might be degraded during fermentation [29].…”
Section: Determination Of Total Phenolic Contentmentioning
confidence: 99%
“…2 d). A similar trend was reported by Zubaidah et al (2020) , which showed an increase of TPC on day 5 in controlled fermentation of white cabbage inoculated with Ln. mesenteroides and L. plantarum strains.…”
Section: Resultssupporting
confidence: 88%
“…Vasiljevic dan Shah (2008) menambahkan bahwa selama fermentasi, BAL dapat menghasilkan komponen metabolit, seperti asam-asam organik yang menyebabkan penurunan nilai pH. Hasil penelitian ini tidak terlalu berbeda dengan hasil penelitian Zubaidah et al (2020) yang melakukan pembuatan sauerkraut dengan penambahan kultur, Leuconostoc mesenteroides, Lactobacillus plantarum serta Lactobacillus plantarum dan Leuconostoc mesenteroides dengan perbedaan jumlah garam sebanyak 0,5% dan 1% menghasilkan pH sebesar 3,4 hingga 2,4.…”
Section: Derajat Keasamanunclassified